Negligence of gingival overgrowth leading to loss of entire dentition - Monali Shah; Vandana Shah; Megha Ellu Poojari; Nishanta Bora (Journal of Indian Society of Periodontology)
Drug-induced gingival enlargement often occurs due to patient’s lack of awareness about the side effects of prescribed medications. This case report details an unusual instance of massive drug-induced gingival overgrowth in a 50-year-old female, successfully managed through a multidisciplinary approach, including surgical intervention and prosthetic rehabilitation. The surgical treatment involved multiple extractions and the excision of excessive tissue. Both arches healed completely after surgery, and the patient underwent prosthetic rehabilitation, with no signs of recurrence. Effective management of such cases relies on patient counseling and appropriate drug substitution. Increasing awareness about the side effects of certain medications and the connection between systemic and oral health is crucial to prevent such cases of gingival enlargement.